Acute hepatitis C in the Netherlands: characteristics of the epidemic in 2014. (February 2016) - Hullegie, S.J.; van den Berk, G.E.L.; Leyten, E.M.S.; Arends, J.E.; Lauw, F.N.; van der Meer, J.T.M.; Posthouwer, D.; van Eeden, A.; Koopmans, P.P.; Richter, C.; van Kasteren, M.E.E.; Kroon, F.P.; et al.
Abstract: Within the Dutch Acute HCV in HIV Study, a surveillance system was initiated to estimate the incidence of hepatitis C virus (HCV) infections in 2014. Following the Dutch HIV treatment guidelines, HIV-positive men having sex with men (MSM) in 19 participating centers were screened. Ninety-nine acute HCV infections were reported, which resulted in a mean incidence of 11 per 1000 patient-years of follow-up. Unfortunately, the HCV epidemic among Dutch HIV-positive MSM is not coming to a halt.